T5 Very low calorie diet in obesity improves metabolic risk factors at the initial cost of ventricular function and steatosis. (21st March 2018) - Rayner, JJ; Peterzan, MA; Neubauer, S; Rider, OJ
Abstract : Background: Very Low Calorie Diets (VLCD) in obesity are an effective weight loss intervention that rapidly reduce liver fat and improve peripheral insulin resistance. We hypothesised that improved peripheral glycaemic control would be accompanied by initial impairment of cardiac function as hepatic fat stores are mobilised and taken up by the myocardium. Methods: 14 obese volunteers (4 male, 49±15 years, BMI 36.2±5.9 kg m-2) underwent body composition analysis and MR scanning for abdominal visceral and liver fat, LV structure and function, 1H-MRS to measure myocardial triglyceride content (MTGC), and echocardiography for diastolic function (E/E'), before and one week into a VLCD (800 kcal/day). Results: 7 days of VLCD led to significant reductions in total body fat, visceral and hepatic fat, and insulin resistance. However, MTGC rose from 1.74±0.99% to 3.02±1.70% (p=0.030), and there was a reduction in both systolic function (LVEF 67±3% to 62±5%, p=0.014; peak radial strain 51±8% to 42±9%, p=0.005) and diastolic function (e/e' 8.5±1.6 to 10.3±3.5, p=0.034). The change in MTGC at one week correlated with change in diastolic function (r=0.729, p=0.017). However at 8 weeks (n=6), changes in MGTC as well as cardiac function had returned to normal. Conclusions: We demonstrate for the first time in healthy obese individuals that a 7 day period of severe caloric restriction results in accumulation of myocardial fat which is associated with impairment of both systolic and diastolic LV function at this timepoint, despite a significant improvement in hepatic fat and whole body insulin sensitivity.